Comparison of blood loss using intra-articular injection of tranexamic acid and without after total knee arthroplasty - Aziz Sabbir Husain (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Total knee replacement (TKR) is one of the most common surgeries in orthopedic field. Up to 1/3 of the patients require blood transfusion post-operative. Allogenic transfusion has many side effects. Tranexamic acid (TXA) is a synthetic antifibrinolytic agent. We explore the usage of TXA in reducing blood loss and transfusion rate by injecting it into the knee joint during surgery. This is a retrospective study done in Hospital Tengku Ampuan Rahimah, Klang. Medical records of patient undergoing TKR between 1st January 2018 till 31st December 2018 were reviewed. Study sample was calculated as 90 patients and divided into 2 groups, one receiving TXA (study) and the other not receiving TXA (control). Post-operative hemoglobin levels and transfusion rate was recorded. 45 patients in study group (17 male, 28 female) had a mean age of 65.4 years old and 45 patients in control group (24 male, 21 female) had a mean age of 64.2 years old. Mean post-operative hemoglobin drop in study group was 1.08 g/dL vs 1.86 g/dL in control group. Repeated measure ANOVA determined a p value of <0.001 which shows a significant correlation. Total transfusion rate in study group was 1 vs 9 in the control group. Using Chi-Square test, the p value was 0.007 which again shows a statistically significant result. Intra-articular injection of TXA following TKR reduces blood loss and the need for blood transfusion without increasing any complication. This prevents many patients from undergoing a potentially hazardous blood transfusion. A routine usage of intra-articular TXA in patients undergoing TKR is recommended. However, a large and well-designed RCT is required to investigate the risk and benefits of TXA.